Tinjauan Siyasah Idariyah tentang Potensi Sistem Big Data dalam Menguatkan Akuntabilitas Pengelolaan Zakat di Badan Amil Zakat Nasional Provinsi Jawa Barat - Alvika Jienni Mulia Pangestuti; Beni Ahmad Saebani; Yana Sutiana (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
A Big Data system involves the management of large-scale data that is integrated with diverse data types and continues to grow by the minute. This system serves as a foundation for decision-making and helps minimize human error. This study aims to analyze the potential of Big Data in Zakat Management at BAZNAS West Java Province to determine whether it adheres to the principles of good public governance according to Siyasah Idariyah or not. Using an empirical legal method, data was collected through interviews and observations with department heads and staff. The findings indicate that BAZNAS West Java has a strong legal foundation; however, the current digital system is not yet optimal for data processing due to integration challenges, technological capacity limitations, and data quality issues that require improvement. From a Siyasah Idariyah perspective, zakat management at BAZNAS West Java already meets the principles of amanah, ‘adalah, and mas’uliyyah regarding information transparency. This study concludes that there is a need to strengthen technological infrastructure, enhance human resource expertise in data analysis and engineering, and adapt policies regarding digital data governance.